2011
DOI: 10.1161/circulationaha.110.014555
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Vasodilator-Stimulated Phosphoprotein Prevents Platelet-Neutrophil Complex Formation and Dampens Myocardial Ischemia-Reperfusion Injury

Abstract: Previously unappreciated, the phosphorylation of VASP performs a key function for the formation of PNCs that is crucially important for the extent of myocardial IR injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
62
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 43 publications
(49 reference statements)
1
62
0
Order By: Relevance
“…Aggregate formation was then induced by adding fMLP (10 mM), 2MeSADP (100 nM), or PAF (10 nM) and incubated for a further 20 minutes at 25°C. The reaction was stopped by adding 2% paraformaldehyde solution in PBS and samples were kept at 4°C until analysis (Rinder et al, 1991;Köhler et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Aggregate formation was then induced by adding fMLP (10 mM), 2MeSADP (100 nM), or PAF (10 nM) and incubated for a further 20 minutes at 25°C. The reaction was stopped by adding 2% paraformaldehyde solution in PBS and samples were kept at 4°C until analysis (Rinder et al, 1991;Köhler et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…These observations may help explain the importance of platelets in promoting leukocyte infiltration into ischemic tissues. 9,32,33 The needle injury model used in this study produces localized injury to endothelial cells that is sufficient to induce a localized and persistent thrombotic response. Although the details of this injury model will be published elsewhere, we found that needle injury does not lead to loss of endothelial cells, but rather to perturbation of their normal antithrombotic function, leading to a-thrombin generation and rapid platelet activation.…”
Section: Blood 30 May 2013 X Volume 121 Number 22 Leukocyte Migratimentioning
confidence: 99%
“…[1][2][3] Platelet inhibition is a key factor in the management of acute myocardial infarction (AMI), and increasingly potent antiplatelet drugs targeting the platelet ADP receptor P2Y 12 have improved patient outcome. 4,5 In addition, the amount of platelets in the ischemic/reperfused myocardium has an important prognostic value.…”
mentioning
confidence: 99%